Behaviour of laterally loaded piles near a slope - Choy, Amos Xian Hao (Nanyang Technological University, 2020)
It is increasingly common to have construction activities beside cut slopes. In this study, a slope is assumed to have already existed for a long time and there is a construction of deep foundation adjacent to the existing slope. Hence, this paper provides a parametric study of soil and pile properties in order to gain a better understanding on the lateral pile capacity beside a slope. An excavation simulation is first carried out to obtain the actual stresses (horizontal, vertical and shear stresses) in the sloping ground, before the foundation is installed. Plaxis 3D is widely used to simulate the behaviour of a long and rigid pile in sands and clays. As such, it is extremely effective in predicting the movements of soil as well as for the displacement of a long and rigid pile. The Hardening Soil (HS) model is selected for all soil models and the slope geometry consists of either clay or sand soil. Some of the parameters considered include type of soil, pile location, pile diameter and slope angle. Further analyses comparing Plaxis 3D and Plaxis 2D are also presented in this paper. Major findings of this study are: (1) slope surface causes a significant reduction in lateral pile capacity by approximately 40% compared to a pile under horizontal surface in both clay and sand. Hence, when designing piles beside a slope, extra care has to be taken to ensure that its lateral capacity is sufficient to resist any lateral load. (2) pile displacement appears to have no changes at a location four times the pile diameter and beyond from the slope crest in clay and three times the pile diameter and beyond in sand. (3) in clay, pile displacement increases with a decrease in slope length (B) with the same lateral load and the influence of slope becomes greater as the slope length decreases (steeper slope). The results also indicate that different slope angle (B=30,35,40) have minimal effects on the pile displacements in sand. In both soils, the shape of displacement curves does not change because of different slopes angles. (4) pile size affects the lateral capacity significantly. Generally, a larger pile size has a larger failure load as a result of its higher bending capacity and passive contact area. The reverse is true for piles with smaller diameters.